ANALISIS KAUSALITAS ANTARA KONSUMSI BATUBARA DAN KONSUMSI BIOMASSA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Arif Setiawan; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
Coal is one of the fossil fuels that can be utilised in various industries including the electric power industry, cement industry, paper industry, steel industry, and other industries. It is approximately 70 percent of Indonesian coal production utilised for the supply of domestic electricity, while 10 percent used for cement production, and the rest utilised for industrial fuel and metallurgical processes. In addition to coal, wood is also another source that is often used among the certain communities as biomass energy source. It is obvious that coal and biomass can be used as energy sources, which can be one of the drivers of economic growth (Gross Domestic Product). Therefore, the shortage of these energy sources can be an obstructive factor for the economic acceleration. The purpose of this study is to figure out the reciprocal relationship between the three variables. The method used in this study is Granger causality. The results indicate that there is a positive relationship between GDP and coal consumption, meaning that the use of coal is influenced by GDP. On the other hand, economic growth may also results in an increase in coal consumption.